Spillover Effects of Tobacco Farms on the Labor Supply, Education, and Health of Children : Evidence from Malawi - Xia, Fang; Deininger, Klaus (Oxford University Press, 2019)
Using data from the Living Standards Measurement Study in Malawi, we examine the spillover effects of tobacco farms on children’s labor supply, education, and health. To address potential endogeneity, the share of tobacco farms in a community is instrumented by the change in tobacco buyers following termination of the intermediate buyer system. We find that, as tobacco cultivation is labor-intensive, children in communities with more tobacco growers spend more time as casual laborers and are less likely to advance to the next grade. Adverse health effects, measured by the likelihood of suffering from illnesses related to green tobacco sickness, are estimated to be larger than previously documented. This affects not only “working-age” children but also children too young to work on tobacco farms. Moreover, exposure to large-scale tobacco cultivation is estimated to reduce the height-for-age z-score of children aged 6–60 months. These findings highlight the importance of raising awareness and taking measures to protect children against green tobacco.